2013
DOI: 10.4172/1948-5956.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chlorambucil-Methionine Conjugate: Novel Anti-cancer Agent against Breast MCF-7 Cell Model

Abstract: Breast cancer is the most common type of cancer in women worldwide and it is the second cause of cancer death after lung cancer. There have been many efforts in producing various pharmaceuticals for breast cancer treatment and among them Nanopharmaceutical Sciences have been extremely of high importance. All the drugs used to treat a cancer were usually shown unpleasant side effects. Chlorambucil is an older antineoplastic (anticancer) drug that is an alkylating agent with many known side effects for the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…It may be concluded that Met may be used as a selective target for detection of tumor cells by Met-dependent phenotype. Therefore, Met as a targeting agent has been conjugated with some drug and imaging delivery systems for cancer therapy and tumor molecular imaging 1921…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded that Met may be used as a selective target for detection of tumor cells by Met-dependent phenotype. Therefore, Met as a targeting agent has been conjugated with some drug and imaging delivery systems for cancer therapy and tumor molecular imaging 1921…”
Section: Introductionmentioning
confidence: 99%
“…These analogs showed significant anticancer activities compare to Chlorambucil. Also Omoomi [15] show the production of a new anticancer conjugate of Chlorambucil-Methionine which is highly effective, and has selective targeting features, as well as the ability to prevent the growth of the breast cancer MCF-7 cell line. Millard and coworkers [16] synthetized Mito-Chlor, a triphenylphosphonium derivative of the CHB which selectively targeting nitrogen mustards to cancer cell mitochondria based on mitochondrial membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…The chemotherapeutic drug chlorambucil (CLB) is a nitrogen mustard derivative used in the treatment of some types of cancer, e.g., Hodgkin and non-Hodgkin lymphoma, as well as chronic lymphocytic leukemia [ 1 , 2 , 3 , 4 ]. The anticancer activity of CLB is based on its alkylation properties that damages the DNA and interferes with its replication.…”
Section: Introductionmentioning
confidence: 99%